3-D dispersion model for simulation of accidental toxic gas releases in a metropolitan area. (March 2021) - Min, Mimi; Park, Junyong; Kang, Chankyu; Jung, Seungho
Abstract: Computational fluid dynamic (CFD) simulations were performed to assess the potential chlorine leak scenario in the super-urban area of South Korea, where the human population density is very high and numerous buildings exist near operational water treatment facilities. Flame acceleration simulator (FLACS) was used to predict the consequence from accidental chlorine releases out of one of the water treatment facilities for the nearby area having a size of 5 km × 3 km approximately. The ability to precisely implement 3-D geometries is crucial for a successful 3-D simulation. Thus, a method was proposed to rapidly and accurately implement geometry by importing computer aided-design (CAD) files provided by a government agency, and processing them using Auto CAD and MicroStation software programs. An accidental release from an 18-ton tank was simulated with three different wind directions to determine the expected evacuation distances. Results from the study showed that the endpoint distances varied depending on the density and arrangement of the buildings. Moreover, we employed physical barriers with varying heights for mitigating the effects of toxic gas releases and simulated how effectively they decreased the concentration of released chlorine. Highlights: Chlorine accidental release in a water treatment facility. CFD simulation for large area of the city of Seoul and the advantage of CFD simulation described. Various heights of physical barrier considered for mitigation measures.